# Solutions of Problems 3 Solution (3.1) a) We shall begin by showing that C1 is a subgroup of C . It is clear that C1 ⊂ C .

It remains to show that C1 is closed, contains the identity, and contains the inverse of every of its elements. Indeed (i) Closure: If z1 , z2 ∈ C1 , i.e. |z1 | = |z2 | = 1, then z1 z2 ∈ C1 because |z1 z2 | = |z1 ||z2 | = 1 (ii) Identity: The identity element is 1 which is clearly in C1 because |1| = 1. (iv) Inverse: × The inverse of an element z ∈ C is z −1 . Moreover since z ¯z = |z |2 , we can express the inverse of z as z ¯ z −1 = 2 . |z | Next to show that every element z ∈ C1 has an inverse, we have to prove that |z −1 | = 1. Using the above equation |z −1 | = | z ¯ |z ¯| |z | 1 |= 2 = 2 = =1 2 |z | |z | |z | |z |
× × ×

because |z | = 1, z ∈ C1 . This concludes the proof that C1 is a subgroup of C . × × The subgroup C1 will be normal in C , if z C1 z −1 ⊂ C1 for every z ∈ C . However, C× and so C1 are abelian groups because z1 z2 = z2 z1 for every pair of complex numbers. Therefore C1 is normal because every subgroup of an abelian group is normal. In this particular case, we have zuz −1 = zz −1 u = u for every u ∈ C1 and z ∈ C . b) The set R+ is a group with multiplication law the standard multiplication of real numbers. We deﬁne a map τ as follows: τ:
×

C× → R+
z → τ (z ) = |z | .

To show that τ is a group homomorphism, we have to prove that τ (z1 z2 ) = τ (z1 )τ (z2 ) 1

we have τ (z1 z2 ) = |z1 z2 | = |z1 ||z2 | = τ (z1 )τ (z2 ) . d) Recall the theorem that has been explained in the lectures which states that if φ : G → G is a group homomorphism onto G with kernel H . H = C1 = Ker τ and G = R+ and ﬁnd that C× /C1 ∼ = R+ . z2 ∈ C . Then τ (z ) = τ (r) = |r| = r . |z2 |) |z1 | |z2 | 2 . one has to prove that for every r ∈ × z ∈ C such that τ (z ) = r. Indeed. e) To show that C× ∼ = C1 × R+ . |z1 ||z2 |) = ( . these are the elements of C1 and so × × R+ there is a C× for which τ (z ) = |z | = 1. then G/H ∼ = G . |z1 |)( . C1 ∼ = Ker τ . The map φ is a group homomorphism. |z | z → φ(z ) = ( The map φ is clearly well-deﬁned. c) The kernel of the homomorphism τ is deﬁned as follows: Ker τ = {z ∈ C : τ (z ) = 1} . We × apply this theorem for G = C . |z |) .for z1 . |z1 z2 |) = ( . we consider the map φ: C× → C1 × R+ z . and the map is onto. i. |z2 |) = φ(z1 )φ(z2 ) . Indeed let z1 = z2 and φ(z1 ) = φ(z2 ). let r ∈ R+ and set z = r. |z1 |) = ( . Indeed. So τ is a group homomorphism.e. Moreover to show that τ is onto. the elements z ∈ Ker τ are the complex numbers in However. |z1 z2 | |z1 | |z2 | |z1 | |z2 | The map φ is 1 − 1. Then by the hypothesis ( z2 z1 . Indeed φ(z1 z2 ) = ( z1 z2 z1 z2 z1 z2 .

b2 ∈ S . but we need to check that composition of maps in S gives maps in S . Since S is a set of maps.0 .) From construction the set S is S = {sa. then a2 a1 = 0. These imply that z1 = z2 . |u||r|) = (u.b1 = sa3 . Then φ(z ) = ( C1 × R+ . we get sa2 . r) ∈ × complex number z = ur ∈ C .b1 (x) = sa2 .b1 .b2 . Solution (3. It remains to deﬁne the group multiplication law on S .b2 ◦ sa1 . sa3 .a2 b1 +b2 .b1 and then with sa2 . So φ is 1 − 1. We can now show that S is a group under the above multiplication law. |ur|) = ( .a2 b1 +b2 = sa3 a2 a1 .b3 · sa2 a1 .b1 ) = sa3 . (ii) Associativity: This follows immediately by the fact that the multiplication law corresponds to composition of maps. Next consider the z ur ur .b2 (a1 x + b1 ) = a2 a1 x + a2 b1 + b2 .b1 := sa2 .a3 b2 +b3 · sa1 .b1 (iii) Identity: The identity is e = s1.b1 = sa1 a2 .b2 · sa1 . b) ∈ R × R}. Therefore φ is a group isomorphism and this proves (e).b for every sa. Explicitly.b3 · sa2 . Indeed let (u. it is natural to deﬁne multiplication by map composition.a2 b1 +b2 .b2 · sa1 .b = sa.b · s1.0 = s1. sa2 .b : (a.2) a. 3 (1) × . so that the multiplication law is sa2 .0 · sa.a3 (a2 b1 +b2 )+b3 = sa3 a2 .b3 · sa2 .b2 · sa1 . It remains to show that φ is onto. contradiction.b ∈ S . |z |) = ( . Let sa1 . r) |z | |ur| |u||r| since |u| = 1 and |r| = r.b2 sa1 . Indeed (i) Closure: It is obvious because if a1 = 0 and a2 = 0. acting on R ﬁrst with sa1 . We see that this is simply sa1 a2 . So φ is onto. Indeed sa.and so z1 z2 = |z1 | |z2 | |z1 | = |z2 | .

respectively.−b ∈ S1 .b = sa. let s1. Therefore S1 is a subgroup of S . Similarly. then s1.0 . and b = 0} = {sa.(iv) Inverse: We take as the inverse of sa.0 ∈ S2 and so the composition law satisﬁes closure.−a−1 = saa−1 .b2 ∈ S1 . (ii) Identity: The identity s1.b1 · s1. we have the following: (i) Closure: Indeed.b ∈ S1 is 1 s− 1.0 . This is indeed the inverse because 1 sa.b = sa−1 . let sa1 . to show that S2 is a subgroup.b1 +b2 ∈ S1 and so the composition law satisﬁes closure. (ii) Identity: The identity s1. we have the following: (i) Closure: Indeed.−aa−1 b+b = s1. b. (iii) Inverse: The inverse of the element s1.0 · sa2 .0 .b2 = s1.−a−1 b .b · sa−1 .0 ∈ S1 .0 of S is an element of S1 .b = sa−1 .0 of S is an element of S2 .a−1 b−a−1 b = s1.−a−1 b · sa. s1. sa2 .b = sa−1 a. and a = 1} = {s1. 4 . then sa1 .b · sa.0 ∈ S2 .b = s1.0 ∈ S2 is 1 s− a.b . a ∈ R − {0}} .) The transformations S1 and the transformations S2 are generated by the following subsets of S : S1 = {sa.0 = sa−1 . which is clearly in S . To show that S1 is a subgroup.b · s− a.b ∈ S the element 1 s− a. b ∈ R} S2 = {sa.b1 .b ∈ S. (iii) Inverse: The inverse of the element sa.0 1 s− a.b ∈ S.0 = sa1 a2 .

we have to prove that 1 sa. The group homomorphism φ is onto. c.b · S1 · s− a.ad+b · sa−1 . Solution (3. ab.0 } = {s1. to show the latter.0 = sa1 .b1 · φ sa2 . such that φ sa.b = sa.−a−1 b = saa−1 .b ∈ S : φ sa.b = sa. Finally the kernel of φ is ker(φ) = {sa.b2 .0 ∈ S2 .0 = s1. Using the theorem that has been described in the lectures. a. The former is obvious.b : b ∈ R} = S1 . say sa. a2 b} . So there are two right cosets.) To show that S1 is a normal subgroup of S . So ker(φ) = {sa. Indeed for every element sa.0 = φ sa1 .b · s1.3) a. So φ is a group homomorphism.0 }. So |S3 | = 6 = r|H | = 2 · 3 5 .d · s− a. we ﬁnd that S/S1 ∼ = S2 .) The right cosets of H in S3 are He = {e.a1 b2 +b1 = sa1 a2 .e.d ∈ S1 . we can ﬁnd an element in S .0 .Therefore S2 is a subgroup as well. i.b ∈ S : φ sa.b → φ sa.b ∈ S . we consider the map φ: S → S2 sa.b2 = φ sa1 a2 .0 · sa2 . c.1 = sa.b = s1.b ⊂ S1 for every sa. having three elements each. Hb = Hab and so on. This map is well deﬁned and a group homomorphism.−b+ad+b = s1.0 . Indeed let s1. we have φ sa1 .b1 · sa2 . Observe that there no other right cosets. The order of S3 is six.ad ∈ S1 . Therefore S1 is a normal subgroup. the index is two.) To ﬁnd the coset group S/S1 .1 ∈ S . a2 } Hb = {b. then 1 sa.b = sa.

b. a2 b} . b. c. Observe that S3 = [e] ∪ [a] ∪ [ab] and so S3 has three conjugacy clases. having three elements each. i. g ∈ S3 . it is the union of two conjugacy classes of S3 and so it is normal. i. b } .) The number of cosets of H in S3 is two. To verify this. let Z2 =< b >= {e . bab−1 } = {a. we expect it to be isomorphic to Z2 .)Observe that the subgroup H is H = [e] ∪ [a] .e. (All are disjoint). a2 b. the index is two. ba2 } = {b.e. So there are two left cosets. so the coset subgroup S3 /H has order two. a2 } bH = {b. The order of S3 is six. Next [a] = {a. From the classiﬁcation theorem. we shall construct a group homomorphism φ: S3 → Z2 6 . Similarly. ab} . bH = abH and so on. do not give new elements in [a] and [ab]. a(ab)a−1 . ba. Recall that the conjugacy classes of G are disjoint. a. Next. a2 (ab)(a2 )−1 } = {ab. It is clear from the deﬁnition that [e] = {e} .) The conjugacy class [h] of an element h ∈ G is [h] = {ghg −1 for every g ∈ G} . a2 } [ab] = {ab. the left cosets are eH = {e. So |S3 | = 6 = r|H | = 2 · 3 and the Lagrange’s theorem holds.and the Lagrange’s theorem holds. d. the rest of the elements of the type gag −1 and g (ab)g −1 . Observe that there no other left cosets.

So using the theorem we learn that S3 /H = Z2 =< [b] > .) Observe that unlike H =< a >. The kernel of φ is Kerφ = {an bm ∈ S3 : φ(an bm ) = e } = {an b0 ∈ S3 } =< a >= H . We then deﬁne the map φ(an b0 ) = φ(an ) = e φ(an b1 ) = φ(an b) = b . [b]} and [b]2 = [e]. Z2 = {[e]. and so generically an bak = a b for some .with kernel H . 7 . So φ is a group homomorphism. we have used the relations ba = a2 b and ba2 = ab of S3 . So they are not normal subgroups of S3 . 0 ≤ n ≤ 2. 0 ≤ n ≤ 1} . e. we have φ(an b0 ak b0 ) ≡ φ(an ak ) = φ(an+k ) = e = φ(an )φ(ak ) φ(an b1 ak b0 ) ≡ φ(an bak ) = φ(a b) = b = φ(an b1 )φ(ak b0 ) φ(an b1 ak b1 ) ≡ φ(an bak b) = φ(a b2 ) = φ(a ) = e = (b )2 = φ(an b)φ(ak b) . b} and {e. the subgroups {e. ab} cannot be written as the union of conjugacy classes of S3 . For this observe that all the elements of S3 can be written as follows: S3 = {an bm . In particular. To show that φ is a group homomorphism.